(untitled) (UNED Research Journal, 2020)
Introduction: The rat (Sigmodon hirsutus) is common in agricultural environments in Central America. Of this species little biological and ecological information is available, given its recent reclassification as a species. Objective: To describe the body morphometry, used in turn as a criterion of body condition and to determine your reproductive cycle of the field rat. Methods: The study was carried out in the canton of La Cruz, Province of Guanacaste, Costa Rica from March 2009 to April 2010. I did 29 fortnightly samplings of three consecutive nights on organic pineapple crops. I measured the length and weight of individuals to establish a relationship between these variables and use them to estimate the body condition index. I determined the reproductive cycle based on the state of pregnancies, presence of juveniles, and in complementary form the testicular position in males. By body characteristics and reproductive activity, age categories were defined. Results: I collected 418 specimens of S. hirsutus, for a sex ratio of 1:0.6 (male:female). Males are bigger and heavier. The body condition index (mm/g) ranged from 1 to 6,4 for males and between 1 and 8,3 for females, with an inverse relationship to the weight category. Of the 154 females collected, 36,4% were pregnant, all of which were present in all months and most often in April 2009, June and August. The presence of juveniles was greatest in April 2009 and June, although they were present in almost every month of the year. The scrotal position of testicles was the most common (54,4%). The age categories being represented throughout the year, suggesting a reproductive activity for the species and site throughout the year. Conclusion: The rat S. hirsutus is of medium size (141,65mm and 84,13g and 131,81mm and 69,07g, for males and females, respectively), and presents sexual dimorphism. Reproductive activity occurs throughout the year.